2011
DOI: 10.1002/app.35166
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pellet size and compatibilization on thermal decomposition kinetic of recycled polyethylene terephthalate/recycled polypropylene blend

Abstract: This study considers the effects of pellet geometry and compatibilization on its moisture absorption and thermal degradation behavior of recycled polyethylene terephthalate (RPET) and recycled polypropylene (RPP) blend with the ultimate goal of optimizing the design of pellets to enhance their processability. The isoconversion of Flynn-Wall-Ozawa (FWO) was used for the kinetic study, which was suitable for thermal degradation of RPET/RPP blend in N 2 while the second order polynomial function was fitted for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…In addition, pellets geometries i.e. size and shape are influenced on moisture absorption of polymers [2,4]. Thumsorn et al [4] showed that finer geometries, such as powders of RPET and recycled polypropylene (RPP) blends, were found to have higher moisture absorption rates due to their large surface area although they could be easily dried.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pellets geometries i.e. size and shape are influenced on moisture absorption of polymers [2,4]. Thumsorn et al [4] showed that finer geometries, such as powders of RPET and recycled polypropylene (RPP) blends, were found to have higher moisture absorption rates due to their large surface area although they could be easily dried.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, recycling of PET bottles offers a very practical solution to reduce landfill waste thus preventing environmental problems. Indeed, there are some researches [2][3][4][5][6][7] about recycled PET (RPET) injection moldings from PET bottles.…”
Section: Introductionmentioning
confidence: 99%
“…It can be noted that degradation temperature at elevated temperature (T d50 ) of the filled RPET composites slightly increased when increasing the fillers contents, which indicated the improvement of thermal stability in the filled RPET composites. The residual from the decomposition corresponded to the additives content and ash from the polymer …”
Section: Resultsmentioning
confidence: 99%
“…Polymer blends and additives have been developed to RPET in order to improve its thermal stability and mechanical properties . Pattabiraman et al discussed on thermal and mechanical properties of virgin PET, recycled PET, and their blends.…”
Section: Introductionmentioning
confidence: 99%